Innovative strategies in utilizing deep learning implementation in elementary schools - Enden Hayati; Ricky Yoseptry (At Turots: Jurnal Pendidikan Islam, 2025)
This study aims to analyze teachers' innovative strategies in the implementation of deep learning-based learning in elementary schools. The background of the research departs from the challenges of 21st century education that demand critical thinking, collaboration, and creativity skills, while learning practices in elementary schools still tend to be conventional and passive. Previous studies have shown the effectiveness of deep learning in improving students' literacy, numeracy, and reflective skills, but aspects of teachers' strategies in the context of elementary schools are still rarely studied. This research uses a qualitative approach with a case study design at SDN Cicalengka 08 and SDN Pelita Bandung Regency. Data was collected through interviews, observations, and documentation, then analyzed with the interactive model Miles, Huberman, and Saldana and tested for validity using triangulation of sources and methods. The results of the study showed that teachers applied innovative strategies through the PDCA (Plan-Do-Check-Act) cycle. Planning is carried out by analyzing student needs and adjusting the curriculum, implementation using active methods such as group discussions, educational games, and interactive media, evaluation includes analytical tests, observations, and projects, while follow-up is in the form of providing feedback and reflection on strategies. The main obstacles include limited facilities, variations in student readiness, time constraints, and suboptimal parental support. The conclusion of this study confirms that innovative strategies based on deep learning are able to increase students' motivation, engagement, and 21st century skills. The novelty of the research lies in the integration of Piaget's theory of cognitive development with the PDCA framework, which produces contextual and participatory strategy models according to the characteristics of elementary school students.